Examination of sailors' balancing ability considering the role of the head movement. (2018) - Kiss, Bernadett; Nagymáté, Gergely; Kiss, Rita M
Abstract: The present study aims to determine the effect of professional sailing on the balancing ability compared to a control group using ultrasound-based unilateral provocation tests on a moving platform. The movement of the platform and the subjects' head movement was also captured during double-limb standing with eyes closed. Another goal of the study was to determine the role of the head movement in the balancing ability. The balancing capacity is characterized by the magnitude of head and platform movement in antero-posterior and medio-lateral directions, and by differences of the head and platform movement in both directions. The magnitude of head movement in antero-posterior direction showed significant differences ( p=0, 039 ) between the examined groups. This means, that the sailor group interferes significantly more with their heads in antero-posterior direction than the control group, so the professional practice of sailing could change the method of balancing.